Occlusion Pressure of the Thoracic Duct in Fontan Patients With Lymphatic Failure: Does Dilatation Challenge Contractility?. Issue 6 (November 2022) - Savla, Jill J.; Kelly, Benjamin; Krogh, Emil; Smith, Christopher L.; Krishnamurthy, Ganesh; Glatz, Andrew C.; DeWitt, Aaron G.; Pinto, Erin M.; Ravishankar, Chitra; Gillespie, Matthew J.; O'Byrne, Michael L.; Escobar, Fernando A.; et al.
Background: The Fontan circulation challenges the lymphatic system. Increasing production of lymphatic fluid and impeding lymphatic return, increased venous pressure may cause lymphatic dilatation and decrease lymphatic contractility. In-vitro studies have reported a lymphatic diameter-tension curve, with increasing passive stretch affecting the intrinsic contractile properties of each thoracic duct segment. We aimed to describe thoracic duct occlusion pressure and asses if thoracic duct dilation impairs contractility in individuals with a Fontan circulation and lymphatic failure. Methods: Central venous pressure and thoracic duct measurements were retrospectively collected from 31 individuals with a Fontan circulation. Thoracic duct occlusion pressure was assessed during a period of external manual compression and used as an indicator of lymphatic vessel contractility. Measurements of pressure were correlated with measurements of the thoracic duct diameter in images obtained by dynamic contrast-enhanced MR lymphangiography. Results: The average central venous pressure and average pressure of the thoracic duct were 17 mm Hg. During manual occlusion, the thoracic duct pressure significantly increased to 32 mm Hg. The average thoracic duct diameter was 3.3 mm. Thoracic duct diameter correlated closely with the central venous pressure. The rise in pressure following manual occlusion showed an inverse correlation with the diameter of the thoracic duct. Conclusion: Higher central venous pressures are associated with increasing diameters of the thoracic duct. When challenged by manual occlusion, dilated thoracic ducts display a decreased ability to increase pressure. Dilatation and a resulting decreased contractility may partly explain the challenged lymphatic system in individuals with a Fontan circulation.